Sejarah Perkembangan Pendidikan Islam Indonesia Sejak Pra-Kemerdekaan sampai Orde Baru - Aulia, Afifah Afra; Abhimanyu, Adjie Anggito; Ranti, Susiana Sofia; Prahesti, Widya Ajeng (Matan : Journal of Islam and Muslim Society, 2023)
Islamic education in Indonesia experienced dynamic development in response to the times. This research aims to describe the development of Islamic education in Indonesia since before the independence of the Republic of Indonesia until the New Order period. The research method used is a literature study. The results showed that Islamic education in Indonesia developed to answer the challenges of modernity to develop individuals. Despite challenges such as discrimination and religious diversity, the government has implemented policies to improve Islamic education and solve problems related to education. Globalisation has changed the direction and purpose of Islamic education, requiring critical thinking skills.